2014
DOI: 10.1108/ijsms-15-04-2014-b005
|View full text |Cite
|
Sign up to set email alerts
|

Strategic match of athlete endorsement in global markets: an associative learning perspective

Abstract: Marketers worldwide consider athlete endorsement a highly effective promotional tool. However, little is known about consumers' responses towards athlete endorsement in global markets - particularly the bi-directional image transfer mechanism. This study examines the image match between athlete endorsers and products using a three-dimensional visual map and comparing image perceptions towards athlete endorsements among respondent groups from Japan, Korea and the United States during the 2010 FIFA World Cup. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The results offer several meaningful theoretical implications. In a similar manner with the theory of selective attention (Machintosh, ; Janiszewski et al ., ; Chang et al ., ; Chang and Ko, 2016), consumers indeed weighed differently on particular sponsor attributes depending on event type in constructing their evaluative judgment (attitude). Specifically, the results of the current study showed that sincerity was not an important sponsor attribute in the profit sport event context, while the same attribute significantly influenced consumers' attitude construction in the nonprofit event sponsorship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results offer several meaningful theoretical implications. In a similar manner with the theory of selective attention (Machintosh, ; Janiszewski et al ., ; Chang et al ., ; Chang and Ko, 2016), consumers indeed weighed differently on particular sponsor attributes depending on event type in constructing their evaluative judgment (attitude). Specifically, the results of the current study showed that sincerity was not an important sponsor attribute in the profit sport event context, while the same attribute significantly influenced consumers' attitude construction in the nonprofit event sponsorship.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of celebrity endorsement, Chang et al . () formulated attentional determinants (i.e., expertise of athlete/product quality, attractiveness of athlete/product design, and popularity of athlete and product) of endorsement effectiveness. The authors compared three distinctive markets (i.e., Japan, Korea, and USA) and found that even for the same endorsement contract, consumers evaluate the endorsement uniquely depending on their attentional focus (e.g., Asians‐expertise vs. Americans‐attractiveness).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The concept of image congruence originates from the match-up hypothesis (Kahle and Homer, 1985), and schema theory is widely considered the best theory to explain the match-up hypothesis (Gwinner and Eaton, 1999;Chang et al, 2014;Huang et al, 2015;Koo and Lee, 2019). A schema is a cognitive structure that reflects a concept or type of stimulus, including its attributes and the relationship among its attributes (Fiske, 1982).…”
Section: Image Congruencementioning
confidence: 99%
“…As such, a wide range of topics related to athlete endorsement has been explored. In particular, the match-up hypothesis has been widely employed to explain the effectiveness of athlete endorsement (e.g., Chang et al , 2014; Koernig and Boyd, 2009; Lee and Koo, 2015). As they align naturally with sports-related brands, athlete endorsers have proven to be quite effective and efficient compared to nonathletes in terms of attitudes toward the advertisement, the brand and purchasing decisions when the product is sports related (Koernig and Boyd, 2009; Lee and Koo, 2015).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Despite a plethora of research on athlete endorser effectiveness in marketing and communication literature, consumers' divisive and equivocal responses toward Nike's campaign cannot be fully explained. To explain the effectiveness of athlete endorsement, scholars have generally employed the match-up hypothesis, which has been proven to be quite effective (e.g., Chang et al , 2014; Koernig and Boyd, 2009; Lee and Koo, 2015). Yet, there exists insufficient empirical research surrounding the effectiveness of endorsers who engage in activism, that is, endorsers who promote progressive change (Presley et al , 2016).…”
Section: Introductionmentioning
confidence: 99%